Dose-dependent histological alterations in the rat lung following intravenous application of Re-188-labeled microspheres. (October 2013) - Haase, Michael G.; Liepe, Knut; Faulhaber, Diana; Wunderlich, Gerd; Andreeff, Michael; Jung, Roland; Baretton, Gustavo B.; Fitze, Guido; Kotzerke, Jörg
Abstract Purpose: The objective of this study was to determine the dose-effect correlation of pneumopathy after application of Rhenium-188 microspheres (Re-188 MS) in an animal model using histological changes as an end-point. Methods and materials: Wistar rats received an intravenous injection of Re-188 MS yielding doses that ranged from ˜ 2 to ˜ 55 Gy. Lungs were removed after ˜ 25 weeks and prepared for histology. Sections were evaluated using a semi-quantitative 5-tiered score. Dose groups of 10 Gy intervals were statistically analyzed using the Chi-square test with respect to grade and extent of connective tissue accumulation, thickness of vessel walls and accumulation of alveolar macrophages (AM). Results: There was a statistically significant increase in connective tissue content and extent in all dose groups compared to control lungs and at least between each other dose group. The steepest increase in connective tissue was at doses higher than 40 Gy. Starting from that dose, a statistically significant increase of AM accumulation and vessel wall thickness occurred. Conclusions: There was a clear dose-effect correlation between radiation dose and histological changes. These findings allow an estimation of potential normal tissue damage especially during tumor treatments of liver lesions with radioactive particles in patients with significant liver-to-lung shunts.